DETERMINATION OF THERMODYNAMIC PARAMETERS OF POLY (VINYL-CHLORIDE) USING INVERSE GAS-CHROMATOGRAPHY - KAYA, I; CEYLAN, K; OZDEMIR, E (Scientific Technical Research Council Turkey, 1995)
Some thermodynamic parameters such as partial molar enthalpy, Delta H-1(s), and molar entropy, Delta S-1(s), for sorption; partial molar free energy, Delta G(1)(infinity), weight fraction activity coefficient, (a(1)/w(1))(infinity), and Flory-Huggins interaction parameter, chi, for poly (vinyl chloride)-n hexane, methylacetate, benzene and toluene systems at infinite dilution were found by using the IGC technique. Also, the solubility parameter of poly (vinyl chloride) at an infinite dilution was found by plotting the graph [(delta(1)(2)/RT) - chi/V-1)] versus solubility parameters of some probes, delta(1).
Keywords: Poly(Ethyl Methacrylate); Solubility Parameters; Dependence; Phase